NILAI – NILAI PENDIDIKAN ISLAM BERBASIS WASATHIYAH PERSPEKTIF MUHAMMAD QURASIH SHIHAB - Isnani Kalinda; Muhammad Asrori; A. Nurul Kawakip (Universitas Islam Negeri Alauddin Makassar, 2022)
Muslim intellectuals studied his views on the concept of wasathiyah (religious moderation). Among these figures is Muhammad Qurais shibab. This character will be the focus of the researcher's study. Muslim intellectuals who have thoughts and views on the wasathiyah concept, this is evidenced by writings such as: Islamic Insights on Religious Moderation, Grounding the Al-Qur'an the function and role of revelation in people's lives, Islam that I adhere to, Insights on the Al-Qur'an thematic interpretation on various problems of the people, Tafsir Al-Misbah. This study aims to describe (1) Muhammad Quraish Shihab's ideas about wasathiyah, and (2) Identify the educational values contained in Muhammad Quraish Shihab's thoughts. This type of research is library research and uses a historical approach and a philosophical approach. The data sources of this research are primary sources, such as works written directly by the character, and secondary sources, such as literature works relevant to the theme raised. documentation study. The data analysis method uses data content analysis techniques. The results of the study are (1) Muhammad Quraish Shihab's ideas about wasathiyah refer to wasathiyah values or moderation, namely based on religious values, this study emphasizes that to determine wasatiyah one must have religious knowledge. (2) The educational values contained in the thoughts of Muhammad Quraish Shihab are: 1) Belief in God (Faith). 2) Morals (Being Submissive). 3) Worship. 4) Social Life. 5) Social Relations.